Comparative safety and efficacy of manual therapy interventions for cervicogenic headache: a systematic review and network meta-analysis - Xu, Xueliang; Ling, Yan (Frontiers in Neurology, 2025)
ObjectiveTo evaluate and compare the safety and efficacy of spinal manipulation, mobilization, and massage for the management of cervicogenic headache (CGH) using meta-analytic techniques.MethodsComprehensive searches were conducted in Cochrane, Embase, PubMed, and ClinicalTrials.gov to identify studies investigating the effects of manipulation, mobilization, and massage on pain, disability, and physical function in patients with CGH. Key outcomes included pain severity (visual analog scale, VAS), Neck Disability Index (NDI), Flexion-Rotation Test (FRT), and Headache Disability Inventory (HDI) at various follow-up timepoints.ResultsFourteen studies totaling 1,297 CGH patients were included. Standard pairwise meta-analysis revealed that sustained natural apophyseal glides (SNAG) mobilization produced significantly greater improvements compared to non-SNAG interventions in VAS (MD = 1.73, 95%CI: 1.05, 2.40), NDI (MD = 8.55, 95%CI: 2.73, 14.37), FRT (MD = −7.22, 95%CI: −9.38, −5.07), and HDI (MD = 9.29, 95%CI: 3.64, 14.95), with benefits maintained over time. Network meta-analysis showed that for VAS improvement, the surface under the cumulative ranking curve (SUCRA) probabilities were: cervical spine manipulation (CSM, 98.9%), mobilization (67.3%), exercise (21.0%), and massage (12.8%). For NDI, the SUCRA scores were: CSM (82.2%), mobilization (57.2%), exercise (6.7%), and massage (53.9%). CSM exhibited significantly greater VAS reductions compared to exercise, massage, and mobilization, while mobilization was superior to exercise and massage for VAS. For NDI, CSM was significantly better than exercise, but no other between-group differences were observed.ConclusionIn patients with CGH, SNAG mobilization can significantly improve pain and function, with benefits maintained in the long-term. Additionally, CSM may be the most effective short-term intervention for reducing pain and disability compared to mobilization, massage, and exercise, although clinician expertise appears to be an important factor.Systematic Review RegistrationDOI: 10.37766/inplasy2025.3.0079.